DEPLOYMENT OF PDCA BY INTEGRATING LEAN MANUFACTURING TOOLS - Azzemou, R.; Noureddine, M. (Journal of Advanced Manufacturing Technology (JAMT), 2021)
The current context of economic competition requires the firms to have a rational organization of its resources. This implies growing productivity and optimizing the management of firm flows, thus contributing to performance improvement. In this context, this article proposes a quality approach in the spirit of "KAIZEN". The adopted way is based on a PDCA deployment by integrating tool of Lean Manufacturing for each step of the PDCA cycle. We applied it to a local SME specialized in leather goods to improve the management of its flows without inducing investments. To measure performance of this firm, specific indicators are used, grouped in process indicators for efficiency and effectiveness and indicators of flows for lead time and flow tension index. Final results improve flow management by reducing operations that do not add value to company.